Coaching Method and Performance of Nurses (Case Study at Regional Hospital of Cibinong At Bogor Regency, West Java Province) - Budi Hartono; Johanes Jakri (UHAMKA Press, 2019)
Nurses can use coaching as the way to empower quality of their skills to have excellent services in hospital. Coaching is a tool that can improve motivation and performance of nurses. The research is aimed to get explanation about the relation of coaching, motivation and performance at a regional hospital. Methodology of this research is correlational study with 30 nurses as respondents. Path analyses are used as statistical tools. The result of this study shows that R² is about 0.704; it means that coaching has a direct, positive and significant impact to motivation and performance of nurses. Motivation has a direct, positive and significant impact to the performance of the nurses (R-value = 0.848). Coaching has an indirect, positive and significant impact to the performance of nurse through job motivation (R-value = 0.737). Conclusions of this study is coaching can increase employee potential related to work motivation, coaching aims at increasing the potential of employees who are performance oriented. Planning, implementation and evaluation of empowerment programs with effective coaching methods can ultimately improve the quality and accountability of employee performance. Result of this research implied that the use of coaching could improve motivation and performance for nurse in the hospital.